Implementation and Implications of Conditional Sentences in English Grammar - Putri, Sri Wahyuni; Rosiana, Wahyu Nurul; Cibro, Diva Rahmawati; Naailah, Shofiiya (Jurnal Dieksis ID, 2024)
This study aims to investigate the role of conditional sentences in English grammar by exploring their structures, functions, and implications in various contexts. The urgency of this research lies in the fact that conditional sentences, despite being crucial for effective communication, often confuse English learners, especially regarding understanding and applying the correct structures. Mistakes in using conditional sentences can lead to communication confusion and errors in conveying ideas or information. This study aims to provide a deeper understanding of conditional sentences and their significance in both everyday and academic communication. The research method employed in this study is library research, where the researcher analyzes various sources related to conditional sentences in English grammar. The instruments used include books, journal articles, and other relevant references to gather information about the structure, function, and usage of conditional sentences in different contexts. The data collection technique used is literature review to understand the implementation of conditional sentences in English grammar and their practical applications in communication. The findings of this study show that conditional sentences play a significant role in effectively conveying complex ideas and hypothetical scenarios. This study also highlights the importance of having a correct understanding of the structure of conditional sentences, as mistakes in their use can affect the clarity and accuracy of communication, whether in personal, professional, or academic contexts.